Tafakkur as the Spiritual Mechanism for Environment Conservation - Akhir, Noor Shakirah Mat (Journal of religious and theological information, 2015)
The tafakkur (reflections) concept in Islam is the best means to educate man's thoughts that will then control man's behavior toward righteousness. The activities of tafakkur involve thinking, emotions, perception, imaginations, and ideas of an individual that will then influence his behavioral development. What is meant by his behavioral development includes his beliefs, tendencies, activities, and good and bad habits. The constant reflections and remembrance of Allah, it is believed, will control each of man's actions. This is based on a Quranic verse: "Those who fear Allah, when a thought of evil from Satan assaults them, bring Allah to remembrance, when lo! they see (aright)!" (al-A'raf 7:201). The first effect of tafakkur is the filling of man's heart and man's thoughts on the realization of Allah's greatness, which in turns result in the best of morality (akhlak). The sustainability involving man's relationship with the other creatures of Allah, or more holistically if seen as this world, is closely related to man's role as khalifah (highest leader, successor, or representative) of Allah on this earth. As such, it has become man's responsibility to lead and administer this world. As such, the tafakkur concept in Islam is the best spiritual mechanism in conserving the environment.